Afferent Connections of Cytoarchitectural Area 6M and Surrounding Cortex in the Marmoset: Putative Homologues of the Supplementary and Pre-supplementary Motor Areas. (13th July 2021) - Bakola, Sophia; Burman, Kathleen J; Bednarek, Sylwia; Chan, Jonathan M; Jermakow, Natalia; Worthy, Katrina H; Majka, Piotr; Rosa, Marcello G P
Abstract: Cortical projections to the caudomedial frontal cortex were studied using retrograde tracers in marmosets. We tested the hypothesis that cytoarchitectural area 6M includes homologues of the supplementary and pre-supplementary motor areas (SMA and pre-SMA) of other primates. We found that, irrespective of the injection sites' location within 6M, over half of the labeled neurons were located in motor and premotor areas. Other connections originated in prefrontal area 8b, ventral anterior and posterior cingulate areas, somatosensory areas (3a and 1–2), and areas on the rostral aspect of the dorsal posterior parietal cortex. Although the origin of afferents was similar, injections in rostral 6M received higher percentages of prefrontal afferents, and fewer somatosensory afferents, compared to caudal injections, compatible with differentiation into SMA and pre-SMA. Injections rostral to 6M (area 8b) revealed a very different set of connections, with increased emphasis on prefrontal and posterior cingulate afferents, and fewer parietal afferents. The connections of 6M were also quantitatively different from those of the primary motor cortex, dorsal premotor areas, and cingulate motor area 24d. These results show that the cortical motor control circuit is conserved in simian primates, indicating that marmosets can be valuable models for studying movement planning and control.